Antibiotic resistance via the food chain: Fact or fiction? - Linda Bester; Sabiha Essack (South African Journal of Science)
The mechanisms that bacteria use to acquire additional genetic material, including genes coding for antibiotic resistance, are principally the secondary pathways that have been described as transformation and conjugation pathways. The farming industry often is reported as a hotspot for antibiotic-resistance reservoirs. In this review, we consider the exposure of food animals during the course of their lifespans to preventative, therapeutic or prophylactic treatment with antibiotic agents. In this context, zoonotic bacteria are commonly recognised as a potential threat to human health, with therapeutic treatment of pathogenic organisms on farms increasing the likelihood of selective antibiotic pressure influencing the commensal flora of the intestines. Existing literature indicates, however, that the effective impact on human health of such interventions in the food production process is still subject to debate.